Prevalence Of Staphylococcus Aureus (SA) And Methicillin Resistant Staphylococcus Aureus (MRSA) In Personnel Of Operation Room Of Shahid Sadoughi Hospital, Yazd, Iran - Mohammad Bagher Khalili; Mitra Moshref; Mohammadreza Sharifi; Maryam Sadeh; Alireza Sazmand (Tehran University of Medical Sciences, 2013)
Background and Aim: Staphylococcus aureus(SA) may cause infection in all body organs. Many personnel and patients in hospitals may become carriers of this species. The aim of this study was to investigate relative frequency of SA and its resistance to Methicillin. Materials and Methods: A couple of swabs were taken from nose and nails of 151 personnels working in operation room of Shahid Sadoughi Hospital in Yazd. Samples were inoculated into Mannitol salt agar medium and S. aureus colonies were antibiogramed to determine the rate of resistance to methicillin. Statistical analyses were performed by chi-square and Fishers' exact test. Results: Overall prevalence of SA was 35.09%(19.2% and 15.9% in noses and nails, respectively). Prevalence of methicillin-resistant SA(MRSA) was 11.92%(5.3% and 6.6% in noses and nails, respectively). Surgeons had the highest, and workers the lowest prevalence of nasal SA carrier rate. In contrast, the nails of servants had the highest, and surgeons the lowest SA carrier rate. No significant difference was found between carrier rate and age, sex and duration of employment. But a meaningful relation was found between type of job and MRSA in both noses and nails. All of the MRSA isolates were sensitive to vancomycin. Conclusion: Since employees of operation room are continuously working with patients undergone operation, screening both the personnel and patients to determine the rate of carriage, preventing transfusions of fore mentioned bacterium is necessary and highly recommended.